1995
DOI: 10.1038/nsb0195-56
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an RNA double helix including uracil-uracil base pairs in an internal loop

Abstract: The crystal structure of the RNA dodecamer 5'-GGACUUUGGUCC-3' has been determined from X-ray diffraction data to 2.6 A resolution. This oligomer forms an asymmetric double helix in the crystal. Four consecutive non-Watson-Crick base-pairs are formed in the middle of the duplex including the first intrahelical U-U (or T-T) pairs observed in an oligonucleotide crystal structure. Two different conformations of U-U pairs are observed in the context of the surrounding sequence. One of these pairs is highly twisted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 16 publications
4
99
0
1
Order By: Relevance
“…As noted above, previous structural data with model duplexes suggested that stacking is disrupted by an internal G•U wobble pair, so that stacking between the P1 and the P1 extension helices might not be expected to be continuous (66)(67)(68)70). This structural picture is supported by the recent x-ray structures of the group I intron (65,71).…”
Section: The Role Of the G•u Pair In Self-splicingmentioning
confidence: 63%
“…As noted above, previous structural data with model duplexes suggested that stacking is disrupted by an internal G•U wobble pair, so that stacking between the P1 and the P1 extension helices might not be expected to be continuous (66)(67)(68)70). This structural picture is supported by the recent x-ray structures of the group I intron (65,71).…”
Section: The Role Of the G•u Pair In Self-splicingmentioning
confidence: 63%
“…It appears that the RNA duplex containing two tandem U-C mismatches in its central positions is very unstable compared with a similar duplex with the U-U mismatches (43). The presence of eight water molecules, four per each U-C pair, bound to stabilize these pairs may be the factor that causes a severe nearly 2-fold widening of the major groove as compared with A-RNA, resulting in duplex destabilization (43). It is tempting to speculate that a similar effect may be the driving force for the CAG repeat duplex destabilization in the SCA1 transcripts.…”
Section: Structures Of the Sca1 Transcripts Are The Same In Cellularmentioning
confidence: 99%
“…Which of the postulated two geometries of the U-C pairs occurs in the RNAs: the U-Cϩ (with the neighboring carbonyl and imino groups involved in the formation of hydrogen bonds) or the neutral U-C pair (with N3-imino proton of U forming a watermediated hydrogen bond to the N3 of C)? Some answers to these questions come from the crystal structures of RNA duplexes containing the U-C pairs (43)(44)(45). It appears that the RNA duplex containing two tandem U-C mismatches in its central positions is very unstable compared with a similar duplex with the U-U mismatches (43).…”
Section: Structures Of the Sca1 Transcripts Are The Same In Cellularmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, only a few short RNA molecules were analyzed by X-ray crystallography (Baeyens, De Bondt & Holbrook, 1995;Betzel et al, 1994;Cruse et al, 1994;Leonard et al, 1994;Holbrook, Cheong, Tinoco & Kim, 1991;Dock-Bregeon et al, 1988;Schindelin et al, 1995;Portmann, Usman & Egli, 1995). One reason for few structural investigations of short RNA's was the lack of a suitable method to produce large amounts of RNA tbr a long time.…”
Section: Introductionmentioning
confidence: 99%